Upper limb biomechanics and dynamics of a core skill on floor exercise in female gymnastics - Brtva, P.; Irwin, G.; Williams, G. K.; Farana, R. (Journal of Sports Sciences, 2023)
This study aimed to increase understanding of the biomechanics and dynamics of the upper limbs during the contact phase of the round-off (RO) performed using three techniques. Twenty female gymnasts performed six successful RO trials in each condition: parallel, T-shape and reverse. Kinetic and kinematic data were collected for each trial. All analyses focused on the contact phase for each hand. Continuous joint profiles examined the dynamics of these tasks as well as the kinetic sequencing. In each case, joint angles, angular velocity, moments and powers at the wrist and elbow joint were reported. Difference between the contact phases of the techniques was examined using a one-way ANOVA SPM. The T-shape technique demonstrated negative power at the wrist during contact; however, the elbow joint compensated with a significantly greater positive power generation during the propulsive phase, suggesting a more effective technique compared to the reduced powers of the reverse and parallel. The order of the peak joint powers during the contact phase, the reverse technique, demonstrated a proximal to distal sequence, in contrast to the distal to proximal for the other techniques. These findings highlight the task-specific coordinative structures during this closed chained action.